Aproximación al estado del arte de la competitividad en las empresas pymes (2022)
The main objective of this research work is to investigate the state of progress of the competitiveness of SMEs in Colombia and the world, reviewing different bibliographic sources on the subject. For this purpose, a monographic research approach was followed, collecting qualitative and quantitative information, where the first phase was to collect all the information on the state of competitiveness in Colombia and the world, and the second phase was a statistical analysis with descriptive and linear regression modeling techniques. The results show that technology, human capital training, quality and innovation are the determining factors in the competitiveness of SMEs.